Herbal Medicine For Immunostimulant In Kebumen Districts: An Ethnobotany Study - Husnul Khuluq; Tri Cahyani; Indra Kurniawan; Estetika Hemas; Navi Agustina; Sofingatun Tia Agustin (Urecol Journal. Part C: Health Sciences, 2021)
In the next few years, humanity will be faced with the Covid-19 pandemic which is not expected to end. Increasing the body's resistance is one of the important efforts to fight the epidemic. Many medicinal plants in our country have the potential to be developed into plants that increase endurance. Ethnobotany has a meaning, namely the study of the use of plants by a certain ethnic group to meet their daily needs, such as meeting the needs of food and medicine. This study aims to find out which plants are efficacious in increasing the body's resistance and how to use them by the community. This study used a snowball sampling method with semi-structured interviews. Respondents were 400 people from 5 sub-districts in Kebumen Regency. There are 28 species of herbal medicine that are used to increase immune system, the most widely used part of the plant is the rhizome (35.7%), the most common processing method is boiling (57.1%), the most common method of use was drunk (85.7%). there are 28 species of herbal medicine that are efficacious to increase immune system.